Swallow-Nest Architectures with Cobalt Molybdate Particulates Fixed Constructed Carbon Nanotube Supports for Stable Sodium-Ion Battery Anode - Zhao, Yixing; Xu, Zhanwei; Fu, Hao; Xiao, Ronglin; Fu, Maosen; Yue, Hao; Huang, Jianfeng (Journal of the Electrochemical Society, 2020)
A swallow-nest architecture is fabricated through in situ prefabricated heating using cobalt molybdate (CoMoO4) as the subject and acid-functionalized carbon nanotubes (AF-CNTs) as the skeleton (CoMoO4/AF-CNT nest). The CoMoO4/AF-CNT nest is fixed via the C-O-Mo bond between the AF-CNT supports and CoMoO4 nanoparticles and hydrogen bonds of neighboring CNTs. The size of CoMoO4 in the CoMoO4/AF-CNT nest is confined to the nanometer level (30 nm), which will lead to negligible nanoscale volume changes during charge and discharge. The swallow-nest architecture can enhance the stability of the electrode, thus accelerating electrolyte penetration and providing fast diffusion channels for charge and Na+ ion transfer. When used as the anode of sodium-ion batteries, the CoMoO4/AF-CNT nest electrodes exhibit a reversible capacity of 151.6 mA h g−1 at the promising current densities of 2.0 A g−1 with degradation rate lower than 5.4 A h g−1 cycle−1 after 2000 cycles.